Extinction risk categorization and first record for Colombia of Cycnoches suarezii (Orchidaceae, Catasetinae) - Lizcano, Alejandro; Sánchez-Cortez, Danny; Trujillo Trujillo, Edwin; Perdomo, Oscar (Instituto de Ecología, A.C., 2024)
Background and Aims: The subtribe Catasetinae (Orchidaceae) is composed of 354 species belonging to eight genera, Catasetum, Clowesia, Cyanaeorchis, Cycnoches, Dressleria, Galeandra, Grobya, and Mormodes, distributed in the Neotropics. The genus Cycnoches encompasses 34 species, of which eleven are known from Colombia. In this article, we report C. suarezii for the first time in this country, assess its extinction risk category following the guidelines of the IUCN, and propose strategies for its protection and conservation. Methods: The populations we report were encountered during botanical expeditions in the Andean-Amazonian foothills in the municipalities Florencia and El Doncello, department Caquetá. Threat categorization was based on the IUCN criterion B, which considers distribution data, number of records, and habitat conservation status. Finally, we conducted a review of conservation experiences developed with other orchids to propose strategies for the protection of C. suarezii and its habitat. Key results: We present the first record of C. suarezii for Colombia, with two populations found in the municipalities Florencia and El Doncello, department Caquetá. With this record, the richness of the genus in Colombia increases to twelve species. We propose the category Endangered (EN) at the global level due to the low number of populations and habitat deterioration caused by deforestation, which has exceeded 20% of the Extent of Occurrence (EOO) in the last two decades. Conclusions: Cycnoches suarezii is summed to the orchid flora of Colombia and the Andean-Amazonian foothills of the Caquetá department. We propose in situ, ex situ, and circa situm strategies for its conservation and that of its habitat.